The effects of pre-season and relationships with physical, physiological, body composition, and load markers: A case study comparing starters versus non-starters from an elite female professional soccer team - Oliveira, R.; Brito, J. P.; Fernandes, R.; Morgans, R.; Alves, S.; Santos, F. J.; Pinto, P.; Espada, M. C. (Medicina, 2023)
Background and Objectives: Research on female soccer players that analyzes playing status is scarce and has previously only examined load monitoring, while other markers, such as physical (i.e., strength, power, and agility), physiological (i.e., maximal oxygen uptake), and body composition (i.e., body fat mass, fat-free mass, body water, and phase angle) markers, warrant further investigation. Thus, the study aims were to (a) compare physical, physiological, body composition, and load markers between starters and non-starters; (b) compare measurements pre- and post-training intervention (five weeks); and (c) analyze any relationships between physical, physiological, body composition, and load markers in an elite female soccer team.